Attrition, Abrasion, Corrosion and Abfraction New Overview of Superficial Teeth Lesions - M. Vambera; E. Gojišová (Czech Dental Chamber, 2007)
The authors present actualized and revised nomenclature and classification for surface teeth lesions. Their objective is the standardization, clarity and aplicability for stomatologists.. The paper describes pathodynamic mechanism in originating surface lesions of teeth. Understanding the pathodynamic mechanism of the origin lesions or their combinations make it possible for the dentist to establish a precise diagnosis and to provide adequate suitable therapy.